2019
DOI: 10.1016/j.palaeo.2017.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Volcanism, redox conditions, and microbialite growth linked with the end-Permian mass extinction: Evidence from the Xiajiacao section (western Hubei Province), South China

Abstract: A new Permian-Triassic boundary microbialite (PTBM) is described from the Xiajiacao section of western Hubei Province, South China. The new microbialite, 3.16 m thick, comprises a thin layer of stromatolite and a thick thrombolite unit. An irregular contact separates the uppermost Permian skeletal packstone from the postextinction stromatolite, but it is not yet possible to discriminate whether it was formed by submarine solution in the wake of ocean acidification or subaerial exposure due to regional regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 78 publications
0
17
0
Order By: Relevance
“…Previous studies have suggested that organic matter of the Chang 7 shale was predominately autogenic aquatic phytoplankton (e.g., algae; Guo et al, ; Ji, Xu, & Song, ; Wang et al, ; Yang & Zhang, ; Yuan et al, ; Zou et al, ). The frequent volcanisms indicated by multiple volcanic ash layers in the studied sections seem to have facilitated microbial blooms in either marine or lack waters (Fang et al, ; Pei, Chen, & Fang, ; Zou et al, ). Flourishing phytoplankton therefore may also have promoted the elevated productivity in Ordos.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have suggested that organic matter of the Chang 7 shale was predominately autogenic aquatic phytoplankton (e.g., algae; Guo et al, ; Ji, Xu, & Song, ; Wang et al, ; Yang & Zhang, ; Yuan et al, ; Zou et al, ). The frequent volcanisms indicated by multiple volcanic ash layers in the studied sections seem to have facilitated microbial blooms in either marine or lack waters (Fang et al, ; Pei, Chen, & Fang, ; Zou et al, ). Flourishing phytoplankton therefore may also have promoted the elevated productivity in Ordos.…”
Section: Discussionmentioning
confidence: 97%
“…shale was predominately autogenic aquatic phytoplankton (e.g., algae; Guo et al, 2014;Ji, Xu, & Song, 2012;Wang et al, 2017;Yang & Zhang, 2005;Yuan et al, 2017;Zou et al, 2019). The frequent volcanisms indicated by multiple volcanic ash layers in the studied sections seem to have facilitated microbial blooms in either marine or lack waters (Fang et al, 2017;Pei, Chen, & Fang, 2019;Zou et al, 2019).…”
Section: Accumulation Mechanism Of Organic Mattermentioning
confidence: 88%
“…10) and the Zuodeng section of Guangxi Province (Fig. 10) exhibit a different kind of sequence with a stromatolite bed at the base and thrombolites in the middle and upper parts (Fang et al, 2017;Pei et al, 2017). The Chongyang section described in this paper, however, was deposited in a little deeper environment adjacent to the northern basin…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Examples include vermicular fabrics in limestones (Zhao et al 2008) as well as fan-and calyx-shaped calcium carbonate precipitates (Woods et al 1999;Woods 2014;Heindel et al 2015). A further striking feature is the abundance of microbialites that developed on carbonate platforms in low-latitude regions of the Paleo-Tethys (Lehrmann 1999;Kershaw et al 1999Kershaw et al , 2012Ezaki et al 2003Ezaki et al , 2008Wang et al 2005;Liu et al, 2007;Wu et al 2007;Yang et al 2011Yang et al , 2019Forel 2013;Lehrmann et al 2015;Wang et al 2016;Adachi et al 2017;Fang et al 2017;Tang et al 2017;Wu et al 2017;Chen et al 2019;Foster et al 2019;Pei et al 2019;Wang et al 2019). The unusual sedimentary features may reflect the persistence of unconventional environmental conditions associated with the end-Permian crisis (Bottjer et al 2008;Chen and Benton 2012), while the widespread proliferation of microbial mats likely resulted from a suppressed ecological competition during this time (Foster et al 2020).…”
Section: Introductionmentioning
confidence: 99%